Knowledge, attitude, and practice towards breast self-examination among women: a web based community study - Kandasamy, Geetha; Almaghaslah, Dalia; Almanasef, Mona; Alamri, Raseel Dhafer Abdulhadi (Frontiers in Public Health, 2024)
Background The most common form of cancer among women is breast cancer in the Kingdom of Saudi Arabia. Thus, the purpose of this study was to evaluate women in Saudi Arabia’s Asir Region, on their knowledge, attitudes, and practices (KAP) regarding breast self-examination (BSE). Methods The research was carried out cross-sectional and conducted from October 2023 to June 2024 in Saudi Arabia’s Asir province. Results Out of 397 study participants, 89 (22.4%) had good knowledge, and 308 (77.6%) had poor knowledge; 185 (46.6%) had a positive attitude, and 212 (53.4%) had a negative attitude 24 (6%) had good practice 373 (94%) had poor practice about breast BSE. According to study participants, social media, 204 (51.4%), radio, television, and newspapers were the best places to learn about BSE. In this study, 316 (79.6%) had heard of BSE. 230 (57.9%) stated that breast cancer patient’s likelihood of survival increases with early detection. Only 231 (58.2%) and 247 (62.2%) agreed that breast cancer is indicated by changes in the color and shape of the breast and retraction/discharge of the breasts, respectively. Out of 147, 24 (16.3%) self-examined just one week after each menstruation. Single (OR = 6.259; 95% CI = 1.790–21.887, p = 0.004) and married (OR = 4.923; 95% CI = 1.509–16.056, p = 0.008), Single (OR = 2.736; 95% CI = 1.248–6.000, p = 0.012) and married (OR = 3.176; 95% CI = 1.734–5.817, p = 0.00) were significantly associated with good knowledge and attitude of BSE, respectively. Illiterates (OR = 0.233; 95% CI = 0.060–0.895, p = 0.034), pre-university (OR = 0.222; 95% CI = 0.092–0.538, p = 0.001), Illiterates (OR = 0.293; 95% CI = 0.114–0.755, p = 0.011), pre-university (OR = 0.462; 95% CI = 0.271–0.788, p = 0.005) are less likely to have good knowledge and attitude compared to college and university educated. Conclusion The study revealed that few women have good knowledge, attitudes, and practices among BSE. In this study, attitude level is high in comparison to knowledge and practice. However, 94% never practiced at all. It is strongly advised that a focus be placed on improving women’s KAP regarding BSE, as well as BSE educational programs in universities and more community service activities such as health campaigns in public places.